Anthroposophical center for physically and sexually abused women through the integration of care farming - Bagarra, Gabrelle P.; Galingan, Zenaida C.; Dul-loog, Vic L. (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
Anthroposophy is a spiritual philosophy founded by Rudolf Steiner, an Austrian philosopher, architect and educator on themes like eurhythmy, medicine and agriculture. It embodies freedom or ethical individualism that promotes physical, mental and spiritual well-being by natural means and creative activities. An anthroposophical center will link two different fields: health and agriculture. The number of physically and sexually abused women has heightened over the years. There are only a few functioning healthcae institutions with good quality services found in the Philippines. Due to the increasing number of VAW-related cases in the Philippines, there are no adequate facilities to cater and assist victims of such violence. Establishing a proper home that fosters healing and recovery is very vital to their behavioral, cognitive and physical welfare. This study propose an agriculture-integrated therapeutic complex where abused women can recuperate and take control of their lives with the aid of horticulture therapy. It will serve as a shelter for these women as they combat the effects of VAW. Care farming is a form of multi-functional agriculture and horticulture therapy where residents can lend their services to the environment as a part of their healing process. The perceived benefits of this activity are in the physical, psychological, cognitive and social aspects. This will also provide these people more opportunities to generate income and produce resources for themselves as well while inside the care of home. With the aid of anthroposophy and care farming, a landscape development can be designed in such a way that will suit the needs of abuse victims.
includes appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Architecture and anthroposophy